Association of obesity with headache among US children and adolescents: Evidence from NHANES 1999-2004 - Bu, Xin-Xin; Zhu, Liang-Hua; Wang, Ze-Mu; Lu, Chao; Chen, Hui; Yu, Di (Frontiers in Endocrinology, 2023)
Background: Children and adolescents increasingly commonly suffer from obesity and headache. It has been confirmed that there is an association between obesity and headache in adults; however, evidence of such an association in paediatric populations is still controversial. Therefore, this study examined the relationship between obesity and headache among children and adolescents in the US. Methods: The cross-sectional data of 3948 participants were obtained from the National Health and Nutrition Examination Survey 1999–2004. Weighted logistic regression models were applied to investigate the association between obesity and headache. Subgroup analysis stratified by sex and age was performed to explore the potential difference in the association of paediatric obesity with headache. The performance of paediatric obesity on headache was assessed by receiver operating characteristic (ROC) curve. Results: The present study involved 3948 participants, of whom 713 (18.1%) had headache. Compared to those without headache, participants with headache tended to be girls and adolescents, have less calcium intake, and have higher levels of body mass index (BMI), C-reactive protein (CRP), serum ferritin and triglycerides (TGs) (all P < 0.05). After fully adjusting for potential confounders, the ORs with 95% CIs for headache were 1.03 (0.58–1.54) and 1.25 (0.68–2.30) for overweight and obese participants in comparison with normal-weight controls, respectively, implying no association of paediatric obesity with headache independent of other potential confounding factors. In addition, although higher odds of headache were noted in girls and adolescents (aged 10–17 years), no statistically significant difference was found across any subgroups. The area under the ROC (AUC) of paediatric obesity on headache was 0.634. Conclusions: In summary, our study indicated that obesity is not associated with headache among US children and adolescents. Further prospective studies with larger sample size are needed to validate our findings.